Dionaea Honeypot Implementation and Malware Analysis in Cloud Environment - Shahrivartehrani, Shahrooz; Zainal Abidin, Shadil Akimi (Journal of Computing Technologies and Creative Content, 2016)
The purpose of this paper is analyzing maliciousattacks in computer networks and the Internet. Dionaea honeypotis deployed on cloud environment to detect and collect malwareattacks by reporting the malwares to external analysis serviceproviders in order to understand the behaviour of maliciousattacks, so malwares can be detected before becoming a seriousthreat in the information technology world.